Corneal nerve regeneration after herpes simplex keratitis: A longitudinal in vivo confocal microscopy study - Moein, Hamid-Reza; Kheirkhah, Ahmad; Muller, Rodrigo T.; Cruzat, Andrea C.; Pavan-Langston, Deborah; Hamrah, Pedram (The ocular surface, 2018)
To evaluate the long-term alterations of corneal nerves in patients with herpes simplex virus (HSV) keratitis using in vivo confocal microscopy (IVCM). Prospective, longitudinal, cross sectional. This study included 16 patients with a history of HSV keratitis and 15 age-matched normal controls. Slit-scanning IVCM was performed in all subjects at baseline and then after a mean follow-up of 37.3 ± 1.7 months in the patient group. Corneal subbasal nerve density and corneal sensation were compared between groups at baseline and follow-up. At baseline, the mean subbasal nerve density was significantly lower in both affected eyes (1.4 ± 0.6 mm/mm2) and contralateral unaffected eyes (6.4 ± 0.7 mm/mm2) compared with the controls (14.1 ± 1.6 mm/mm2; all P < .001). At the end of follow-up, the mean nerve density in affected eyes increased to 2.8 ± 0.7 mm/mm2 (P = .006), with no significant change in contralateral unaffected eyes (6.5 ± 1.0 mm/mm2, P = .72). However, both eyes had lower nerve density than controls (all P < .001). Corneal sensation was significantly lower in affected eyes (2.6 ± 0.6 cm) than in the control group (6.0 ± 0.0, P < .001) and showed no significant change at the end of follow-up (2.5 ± 0.6 cm, P = .80). Corneal sensation in contralateral unaffected eyes was not different in comparison with controls at both baseline and follow up (all p > .05). Our results demonstrate that although corneal nerve regeneration occurs in patients with HSV keratitis, this change is not clinically significant and does not results in changes of corneal sensation. Therefore, these patients need to be followed closely for complications of neurotrophic keratopathy and might benefit from neuro-regenerative therapies.